KUALITAS KERJA DALAM PERSPEKTIF MANAJEMEN SYARIAH - Hulaify, Akhmad (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2019)
The quality of work in the perspective of Sharia Management in this research is classified into qualitative research with the nature of library research. The approach model used in this study is divided into two parts, namely the Sociology approach and the normative approach model. Thus to facilitate this research researchers divide the data into two types, namely primary data and secondary data. Then for the sake of the fluency of this research, researchers divided the data collection method into two parts, namely observation, and documentation. After that, to enter into a conclusion the researcher uses the "Comparative Interpretative" analysis method. The final results of this study can be concluded that to realize the quality of work of a worker in his work in a company or the like twelve methods are needed in the study of Sharia Management, namely (right promise, responsibility, worship, jihad, maintaining work unity, being fair, transparency, cooperation, competence, maintaining productivity). Keywords; Quality, Work, Management, Sharia